Genome-Resolved Metaproteomic Analysis of Microbiota and Metabolic Pathways Involved in Taste Formation During Chinese Traditional Fish Sauce (Yu-lu) Fermentation - Wang, Yueqi; Wu, Yanyan; Li, Chunsheng; Zhao, Yongqiang; Xiang, Huan; Li, Laihao; Yang, Xianqing; Chen, Shengjun; Sun, Leilei; Qi, Bo (Frontiers in Nutrition, 2022)
Complex microbial metabolism is key to taste formation in high-quality fish sauce during fermentation. To guide quality supervision and targeted regulation, we analyzed the function of microbial flora during fermentation based on a previously developed metagenomic database. The abundance of most identified genes involved in metabolic functions showed an upward trend in abundance during fermentation. In total, 571 proteins extracted from fish sauce at different fermentation stages were identified. These proteins were mainly derived from Halanaerobium, Psychrobacter, Photobacterium, and Tetragenococcus. Functional annotation revealed 15 pathways related to amino acid metabolism, including alanine, aspartate, glutamate, and histidine metabolism; lysine degradation; and arginine biosynthesis. This study demonstrated the approaches to identify microbiota functions and metabolic pathways, thereby providing a theoretical basis for taste formation mechanisms during traditional fish sauce fermentation.